Yellowknife Old Town -- photograph ... - Seale, Linda N. (University of Alberta Library, 1965)
Yellowknife Old Town, looking east from Akaitcho Hall. Franklin Avenue centre, Back Bay to the left, Latham Island centre distance, Yellowknife Bay to the right. September 1965 ...